Research methods in education - Cohen, Louis (London, United Kingdom : Routledge, 2011)
It continues to be the go-to text for students, academics and researchers who are undertaking, understanding and using educational research, and has been translated into several languages. It offers plentiful and rich practical advice, underpinned by clear theoretical foundations, research evidence and up-to-date references, and it raises key issues and questions for researchers planning, conducting, reporting and evaluating research
Part 1. The context of educational research -- Part 2. Planning educational research -- Part 3. Styles of educational research -- Part 4. Strategies and instrument for data collection and researching -- Part 5. Data analysis
Includes bibliographical references and index.
Keywords: EDUCATION RESEARCH